2014
DOI: 10.1111/cdoe.12114
|View full text |Cite
|
Sign up to set email alerts
|

Dentist‐specific effects on the longevity of dental restorations

Abstract: Public dental officers in Norway show a high degree of homogeneity with regard to longevity of restorations. Further improvements in the longevity of restorations can most likely be achieved by preventing secondary caries and by improving the physical properties of materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…Significant differences in antibiotic prescribing behaviour in the absence of signs of spreading infection or systemic involvement existed between practitioners, even after patient, practitioner and consultation characteristics were controlled for. Indeed, the dentist-specific effects in the current study were greater than those reported in other studies of diagnosis of caries and longevity of dental restorations (33,34), suggesting wide variability in antibiotic prescribing practices amongst this group. Whilst it is vital that judicious antibiotic use is supported and encouraged across the profession, identifying and targeting practitioners who routinely prescribe antibiotics inappropriately may prove the most time-and cost-effective way of improving prescribing.…”
Section: Discussioncontrasting
confidence: 76%
“…Significant differences in antibiotic prescribing behaviour in the absence of signs of spreading infection or systemic involvement existed between practitioners, even after patient, practitioner and consultation characteristics were controlled for. Indeed, the dentist-specific effects in the current study were greater than those reported in other studies of diagnosis of caries and longevity of dental restorations (33,34), suggesting wide variability in antibiotic prescribing practices amongst this group. Whilst it is vital that judicious antibiotic use is supported and encouraged across the profession, identifying and targeting practitioners who routinely prescribe antibiotics inappropriately may prove the most time-and cost-effective way of improving prescribing.…”
Section: Discussioncontrasting
confidence: 76%
“…The longevity of dental restorations has been the focus of much research and debate (Forss and Widstrom 2004; Kolker et al 2005; Burke and Lucarotti 2009; Opdam et al 2011; Demarco et al 2012; Astvaldsdottir et al 2015; Demarco et al 2015; Dobloug and Grytten 2015; Moraschini et al 2015; Laske et al 2016; Schwendicke et al 2016), but many published studies evaluated restorations placed in the general population and thus did not account for the challenges faced by frail older adults. These challenges are numerous and include systemic health, oral health, and social factors.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Tooth-restoration complex failures may occur either in the restorative material or the tooth itself, or both. Restorations are likely to fail mechanically, such as bulk fracture, staining, loss of retention and deficient marginal adaptation [6,7]. In contrast, tooth failures are correlated to mechanical, structural and biological reasons (caries associated with restorations and sealants {CARS} and fractured cusps) [1,5].…”
Section: Introductionmentioning
confidence: 99%